A study on author ranking - Haq, Md. Adnanul; Islam, Md. Noushin; Jeba, Labiba Tasfiya; Prome, Iffat Afsara; Roy, Palash Ranjan (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.